Formation and evolution of biogenic secondary organic aerosol over a forest site in Japan. Issue 1 (8th January 2014) - Han, Yuemei; Iwamoto, Yoko; Nakayama, Tomoki; Kawamura, Kimitaka; Mochida, Michihiro
Abstract [1] Chemical composition of atmospheric aerosol particles was characterized using an Aerodyne high‐resolution time‐of‐flight aerosol mass spectrometer at a forest site in Japan during 20–30 August 2010. A major fraction of nonrefractory submicron aerosol particles consisted of organics (accounting for, on average, 46% of total mass), sulfate (41%), and ammonium (12%). Positive matrix factorization of high‐resolution organic aerosol mass spectra identified two oxygenated organic aerosol (OOA) components: a highly oxidized, low‐volatility OOA and a less oxidized, semivolatile OOA (SV‐OOA), interpreted mainly as aged regional organic aerosol (OA) and as locally formed biogenic secondary OA (BSOA), respectively. The mass concentrations of SV‐OOA increased prominently during the daytime, suggesting a strong photochemical production of BSOA on both nonevent and new particle formation event days. Increases of f44 (fraction of m/z 44 in OA mass spectrum), the fraction of CxOy+ fragment, and the O/C ratio after midday (around 13:00 local time) suggest that OA became increasingly oxygenated, which can be explained by the aging of freshly formed BSOA. Aqueous phase oxidation reactions under conditions of high relative humidity may have played a vital role in the aging of BSOA in this forest atmosphere. A substantial increase of the mass concentration of organics in the small size range (below 300 nm in vacuum aerodynamic diameter), without an increase in that of sulfate, suggests that the formation of BSOA made a dominant contribution to the presence of particles of cloud condensation nuclei size around the studied area.